Varieties of Data-Centric Science: Regional Climate Modeling and Model Organism Research. Issue 4 (10th October 2022) - Lloyd, Elisabeth; Lusk, Greg; Gluck, Stuart; McGinnis, Seth
Abstract: Modern science's ability to produce, store, and analyze big datasets is changing the way that scientific research is practiced. Philosophers have only begun to comprehend the changed nature of scientific reasoning in this age of "big data." We analyze data-focused practices in biology and climate modeling, identifying distinct species of data-centric science: phenomena-laden in biology and phenomena-agnostic in climate modeling, each better suited for its own domain of application, though each entail trade-offs. We argue that data-centric practices in science are not monolithic because the opportunities and challenges presented by big data vary across scientific domains.